Transforming Luxury Jewelry Customer Experience using Strategic Connection Framework in Omnichannel Environments - Yuliia Husarova (Journal of Consumer Sciences, 2026)
Background: To alter the customer experience of the luxury jewellery in an omnichannel setting, behavioural decision-making mechanisms that cannot be reflected in quantitative measures, need to be identified. Purpose: This paper aimed to determine how luxury jewelry omnichannel navigation is controlled and to demonstrate how the Strategic Connection Framework (STRC) can transform customer experience and resolve exclusivity-omnichannel tension. Method: A qualitative comparative case study of luxury jewellery enterprises in the United States and Ukraine. The study covers the whole customer journey from inquiry to transaction. Detailed analysis of customer-consultant interactions and communication records from physical and digital channels provided insights. Three omnichannel maturity models (low, medium and high) were created considering digital integration, channel coordination and consumer behaviour trends in both markets. Findings: The results indicate that they are three mechanisms namely exclusivity-calibration (EXCL), trust-transference (TRST), and ritual-preservation (RITU). STRC incorporates these processes to revolutionize customer experience. Specific differences in the market were observed: the U.S. market is characterized by system-based integration, whereas Ukraine is based on consultative models based on communication. Conclusions: STRC offers a feasible model to transform luxury jewelry omnichannel customer experience under various conditions in the market without eroding exclusiveness. Research implication: The managers of luxury brands are advised to create digital platforms that convey exclusivity, a consistent set of trust cues in all touchpoints, and alter consumption rituals because market-specific logics demand different strategies of implementation.